Implementation of Islamic Communication Ethics In the program Da’wah Bil Lisan on KPI TV UINFAS Bengkulu - Arifin, As'ad Syamsul; Kusuma, Wira Hadi (UIN Fatmawati Sukarno Bengkulu, 2024)
This study aims to determine the application of the oral da'wah method on KPI TV UIN FAS Bengkulu, by examining the da'wah content on the KPI TV UIN FAS Bengkulu YouTube account in 2023-2024 with the most viewers. The approach used in this study is qualitative with a type of relational content analysis, also known as semantic network analysis. The results of the study show that in general the da'wah methods used by da'i in da'wah content on YouTube KPI TV UINFAS Bengkulu include six main methods, namely: Qaulan Layyinan, Qaulan Ma'rufa, Qaulan Karima, Qaulan Baligha, Qaulan Maysura, and Qaulan Sadida. The most frequently used methods are Qaulan Layyinan and Qaulan Ma'rufa. It's just that there are several elements that dominate, because the gentle approach and the use of good words are considered more effective in attracting attention and building audience awareness. This shows that oral preaching through KPI TV is carried out politely, adaptively, and relevant to Islamic values.